2017
DOI: 10.1111/sed.12400
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bed‐scale spatial patterns in dolomite abundance during early dolomitization: Part I. Mechanisms and feedbacks revealed by reaction–transport modelling

Abstract: Dolomites of varied ages exhibit metre-scale nested patterns of lateral periodic variation in permeability and porosity and, by inference, dolomite abundance as most examples are 100% dolomite. Two-dimensional reaction-transport modelling simulations of bed-scale dolomitization were used to assess whether those patterns in dolomite abundance could form during near-surface replacement dolomitization. Simulations used a 2 m high and 18 m long model domain, a low-Mg calcite grainstone precursor and an evaporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 58 publications
(121 reference statements)
1
25
0
Order By: Relevance
“…In general, RTM simulations model the change in porosity due to mineral transformations, dissolution and precipitation, but permeability is inferred, most commonly using the Carmen--Kozeny relationship. Simulations of dolomitisation by Budd and Park (2017), have shown the effect of the positive feedbacks resulting from diagenetic porosity enhancement on replacement of calcite with dolomite. Heterogeneity in initial porosity and permeability fields, and consequent focusing of reactive fluids, results in the development of pronounced perturbations in the geometry of the dolomite front.…”
Section: Challenges In Reactive Transport Modelling Of Syn--depositiomentioning
confidence: 99%
“…In general, RTM simulations model the change in porosity due to mineral transformations, dissolution and precipitation, but permeability is inferred, most commonly using the Carmen--Kozeny relationship. Simulations of dolomitisation by Budd and Park (2017), have shown the effect of the positive feedbacks resulting from diagenetic porosity enhancement on replacement of calcite with dolomite. Heterogeneity in initial porosity and permeability fields, and consequent focusing of reactive fluids, results in the development of pronounced perturbations in the geometry of the dolomite front.…”
Section: Challenges In Reactive Transport Modelling Of Syn--depositiomentioning
confidence: 99%
“…Budd & Park () used bed‐scale reaction‐transport modelling (RTM) to assess the second hypothesis – formation of lateral pattern during dolomitization of a carbonate precursor. These authors found that pattern did emerge at the metres‐scale in the abundance of dolomite, with randomly distributed heterogeneities in the initial calcite reactive surface area (RSA) triggering pattern development.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic illustrating the feedbacks between (A) high and (B) low reactive surface area (RSA), calcite dissolution dolomite precipitation, fluid flow, and development of pods of high and low dolomite abundance. Modified from Budd & Park ().…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations